The Influence Of Product Support On Herd Behavior And Brand Attitude: Direct Impact On Purchase Intention Of Scarlett Whitening - Fiekha Arjunie; Asma’I Ishak (Cita konsultindo, 2024)
This study aims to determine the role of herd behavior and brand attitudes on the influence of product support on purchase intentions on Scarlett Whitening products. The population in this study were Indonesian citizens who had known or used Scarlett Whitening products. The results of an online survey using an online questionnaire with a google form obtained a sample of 380 respondents. In this study, AMOS 29 software was used to analyze all data. The variables used in this study were Electronic Word of Mouth, Celebrity Credibility, Source Congruence, Herd Behavior, Brand Attitude, and Purchase Intention. The results obtained from this study indicate that Celebrity Credibility influences Herd Behavior and Brand Attitude influences Purchase Intention.